Additive forming process of a homogenous heterogeneous stainless steel

CN122252747BActive Publication Date: 2026-10-23CHINA WEAPON SCI ACADEMY NINGBO BRANCH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610737322.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-23
Estimated Expiration
2046-05-27

AI Technical Summary

Technical Problem

常规强化手段提升材料强度的同时,会伴随着塑性的下降,导致材料在服役过程中具有突发性断裂倾向,安全风险系数陡增

Benefits of technology

[0019]优选地,所述构件的抗拉强度≥530MPa,屈服强度≥350MPs,延伸率≥60%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122252747B_ABST
    Figure CN122252747B_ABST
Patent Text Reader

Abstract

The application relates to an additive forming process method of homogenous heterogeneous stainless steel, which adopts electric arc additive manufacturing, utilizes electric arc melting of stainless steel wire materials, and is sequentially fused and accumulated in a double-path single-arc rectangular reciprocating path or a double-path multi-arc rectangular reciprocating path, in each layer, a second path molten pool partially covers the edge of a solidified welding path of a first path to form an overlapping area; and when single-layer deposition is completed and the temperature of the layer is 130-180 DEG C, the next layer is continuously deposited until completion, and a homogenous heterogeneous stainless steel component is obtained. The application can realize good matching of the strength and plasticity of the stainless steel, and cooperatively improves the mechanical properties of the stainless steel as a whole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of stainless steel manufacturing technology, and specifically relates to an additive forming process method for homogeneous and heterogeneous stainless steel. Background Technology

[0002] High-strength stainless steel has become an important material in energy, chemical, marine engineering, aerospace, and defense equipment fields due to its excellent strength, corrosion resistance, and comprehensive mechanical properties. As modern equipment develops towards larger size, lighter weight, and longer service life, stringent requirements are placed on the performance of structural materials: that is, materials must possess both extremely high strength and good plasticity under extreme loads, corrosion, or low-temperature environments.

[0003] Within the framework of traditional materials science, the strength and ductility of metallic materials often exhibit an inverse relationship, where one increases while the other decreases. Conventional strengthening methods, while improving material strength, often result in a decrease in ductility, leading to a tendency for sudden fractures during service and a sharp increase in safety risks. This fundamental contradiction has become a bottleneck restricting the performance improvement of high-end equipment.

[0004] Within a single material, constructing a multi-scale, non-uniform microstructure through process design offers a new approach to overcoming the aforementioned inverse relationship between strength and plasticity. For example, introducing gradient-distributed fine-grained regions into a coarse-grained matrix allows the coarse-grained regions to absorb energy through coordinated deformation, providing plasticity, while the fine-grained regions hinder dislocation movement, achieving high strength. The synergistic effect of these two regions achieves a balance between strength and high plasticity. In materials manufacturing, the realization of homogeneous heterogeneous structures typically relies on complex casting, rolling, quenching, and tempering processes—common thermomechanical treatments. For example, Chinese invention patent application CN202110819295.5 and publication number CN113649413A discloses a method for preparing sheet-like homogeneous lightweight alloy plates by an asymmetric cumulative rolling process; Gao Q, Kou Z, Zhou C, et al. Exceptional strength-ductility synergy in a casting multi-principal element alloy with ahierarchically heterogeneous structure[J]. Materials Today, 2024, 81: 70-83. Through composition design, a multi-principal element alloy with a hierarchically heterogeneous structure was successfully prepared in the as-cast state, and excellent strength-ductility matching was achieved.

[0005] Additive manufacturing, commonly known as 3D printing, is a technology that uses 3D model data to build solid parts by adding materials layer by layer. Compared to traditional casting and rolling processes, additive manufacturing has significant advantages such as high freedom of structural design, no need for molds, short production cycle, high material utilization, and controllable microstructure and properties. If additive manufacturing can be used to overcome the limitations of traditional casting and rolling in achieving uniform microstructure and preparing complex-shaped components, it has significant engineering application value. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide an additive forming process for homogeneous and heterogeneous stainless steel in view of the current state of the prior art, so as to achieve a good match between the strength and plasticity of stainless steel and to synergistically improve the mechanical properties of stainless steel as a whole.

[0007] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: an additive forming process method for homogeneous and heterogeneous stainless steel, which adopts electric arc additive manufacturing, uses an electric arc to melt stainless steel wire, and deposits it layer by layer according to a double-track single-arc rectangular reciprocating path or a double-track multi-arc rectangular reciprocating path. In each layer, the second molten pool partially covers the edge of the first solidified weld bead, forming an overlap area; and when the single-layer deposition is completed and the temperature of the layer is 130~180℃, the next layer continues to be deposited until the process is completed, thereby obtaining a homogeneous and heterogeneous stainless steel component.

[0008] This invention employs arc additive manufacturing and controls the additive path to coordinate heat input (arc heat) and interlayer cooling, maintaining the interlayer temperature within a specific range of 130-180°C before depositing the next layer. This causes localized remelting of the previous layer's surface due to the thermal effects of the subsequent deposited layers and the arc, followed by rapid solidification that forms fine equiaxed crystals in the remelted area. Simultaneously, the adjacent heat-affected zone undergoes significant grain coarsening under thermal cycling. This process is repeated layer by layer with each deposition, ultimately forming a layered, multi-scale heterogeneous structure with alternating coarse and fine grain regions along the component's deposition direction. By designing the additive manufacturing path as a double-pass single-start rectangular reciprocating path or a double-pass multi-start rectangular reciprocating path, and in each layer, the second molten pool partially covers the edge of the first solidified weld bead to form an overlap area. The overlap area undergoes multiple layers of repeated remelting, i.e., rapid heating and cooling, multiple grain breakage and recrystallization, and repeated solid-liquid phase transformation, ultimately forming an overlapping fine-grained region in the middle of the component, with the above-mentioned coarse-grained region and fine-grained region arranged alternately on both sides in a layered multi-scale heterogeneous structure.

[0009] The overlapping fine-grained region in the middle of the component achieves a synergistic improvement in strength and plasticity. In the layered multi-scale heterogeneous structure on both sides of the component, where coarse-grained and fine-grained regions alternate, the coarse-grained region coordinates deformation to provide plasticity, while the fine-grained region hinders dislocation movement to achieve strength. Ultimately, this fundamentally reconciles the contradiction between strength and plasticity, enabling the component to achieve high strength while maintaining excellent plastic deformation capacity and toughness.

[0010] The temperature of 130~180℃ is preferably the temperature at the center of the rectangle.

[0011] Preferably, the process parameters for arc additive manufacturing are: welding torch moving speed of 5~10mm / s, wire feeding speed of 4~8m / min, shielding gas of CO2 or pure Ar, gas flow rate of 15~25L / min, and dry extension of 12~20mm.

[0012] Increasing the moving speed of the welding torch can improve the cooling rate after melting, which is beneficial to the formation of the aforementioned coarse and fine grain regions.

[0013] The above process parameters are adjusted based on cooling. During the initial additive manufacturing process, due to the low number of layers and proximity to the substrate, the cooling rate is too fast. Therefore, it is necessary to increase the wire feed rate to control the subsequent cooling rate. When the number of layers is too high, the wire feed rate can be adjusted to the normal range to ensure that the interlayer temperature of the component remains stable throughout the entire stacking process.

[0014] Preferably, the stainless steel wire is dried at 70-120°C for 3-5 hours before arc additive manufacturing. This prevents moisture adsorbed on the wire surface from causing porosity defects in the component during the additive manufacturing process.

[0015] Preferably, in the component, the middle part composed of the overlapping area of ​​each layer is a uniform fine-grained structure, and the two sides of the middle part are coarse-grained areas and fine-grained areas are alternately distributed along the stacking direction.

[0016] Preferably, the grain size of the coarse-grained region is 1300~1800μm, and the grain size of the fine-grained region is 200~450μm.

[0017] Preferably, the stainless steel wire comprises the following components by mass percentage: C ≤ 0.05%, N: 0.2-0.5%, Mn: 0.3-0.6%, Mo: 0.05-0.3%, Cr: 19-25%, Ni: 9-14%, S ≤ 0.003%, P ≤ 0.003%, O ≤ 0.003%, and Fe as the balance.

[0018] Nitrogen (N), as a solid solution strengthening element, causes severe lattice distortion when incorporated into austenitic stainless steel, significantly increasing its strength. Simultaneously, N is a more potent austenite stabilizer than Ni, partially replacing it. This stabilizes the austenitic structure while reducing production costs. Most importantly, through a dual mechanism of solute drag and Zener pinning effects, combined with the additive manufacturing path and interlayer temperature control described in this application, N inhibits columnar grain growth in the remelted zone (which undergoes rapid solidification) of the previous stage during the subsequent arc pass, and hinders grain boundary migration and grain coarsening in the non-remelted zone (which undergoes repeated thermal cycling). This exacerbates the microstructural differences between the "fine-grained remelted zone" and the "coarse-grained heat-affected zone" at the microscale. This intense microstructural heterogeneity induced by N, combined with the additive manufacturing process of this application, promotes the formation of a homogeneous heterogeneous structure within stainless steel components.

[0019] Preferably, the component has a tensile strength ≥ 530 MPa, a yield strength ≥ 350 MPs, and an elongation ≥ 60%.

[0020] Compared with existing technologies, the advantages of this invention are as follows: By employing arc additive manufacturing and controlling the additive path, this invention coordinates heat input (arc heat) and interlayer cooling, maintaining the interlayer temperature within a specific range of 130~180℃ before depositing the next layer. This causes localized remelting of the surface of the previous layer due to the thermal effects of the subsequent deposited layers and the arc, followed by rapid solidification, resulting in fine equiaxed crystals in the remelted area. Simultaneously, the adjacent heat-affected zone undergoes significant grain coarsening under thermal cycling. This process is repeated layer by layer with each deposition, ultimately forming a layered multi-scale heterogeneous structure with alternating coarse and fine grain regions in the component deposition direction. By designing the additive manufacturing path as a double-pass single-start rectangular reciprocating path or a double-pass multi-start rectangular reciprocating path, and in each layer, the second molten pool partially covers the edge of the first solidified weld bead to form an overlap area. The overlap area undergoes multiple layers of repeated remelting, i.e., rapid heating and cooling, multiple grain breakage and recrystallization, and repeated solid-liquid phase transformation, ultimately forming an overlapping fine-grained region in the middle of the component, with the above-mentioned coarse-grained region and fine-grained region arranged alternately on both sides in a layered multi-scale heterogeneous structure.

[0021] The overlapping fine-grained region in the middle of the component achieves a synergistic improvement in strength and plasticity. In the layered multi-scale heterogeneous structure on both sides of the component, where coarse-grained and fine-grained regions alternate, the coarse-grained region coordinates deformation to provide plasticity, while the fine-grained region hinders dislocation movement to achieve strength. Ultimately, this fundamentally reconciles the contradiction between strength and plasticity, enabling the component to achieve high strength while maintaining excellent plastic deformation capacity and toughness.

[0022] The homogeneous stainless steel of the present invention has excellent tensile properties, with a tensile strength of over 530 MPa, a yield strength of over 350 MPa, and an elongation of over 60%. Attached Figure Description

[0023] Figure 1 This is a metallographic microstructure image of the stainless steel component obtained in Example 1 of the present invention. Figure 2 This is a schematic diagram of the additive manufacturing path in Embodiment 1 of the present invention; Figure 3 This is a metallographic microstructure image of the stainless steel component obtained in Example 2 of the present invention. Figure 4 This is a metallographic microstructure image of the stainless steel component obtained in Example 3 of the present invention. Figure 5 These are schematic diagrams of the tensile specimens in various embodiments of the present invention; Figure 6 This is a schematic diagram of the grain gradient distribution of the tensile specimens in various embodiments of the present invention; Figure 7 This diagram illustrates the formation and grain gradient distribution mechanism of homogeneous and heterogeneous stainless steels in various embodiments of the present invention. Detailed Implementation Example 1

[0024] The austenitic stainless steel flux-cored wire was dried in a drying oven at 100℃ for 3 hours. The stainless steel flux-cored wire comprises the following components by mass percentage: C≤0.05%, N: 0.2-0.5%, Mn: 0.3-0.6%, Mo: 0.05-0.3%, Cr: 19-25%, Ni: 9-14%, S≤0.003%, P≤0.003%, O≤0.003%, and Fe as the balance.

[0025] Then, due to the inherent characteristics of the flux-cored wire, arc additive manufacturing is performed using the FCW-HardFacing mode of the Fronius-CMT welding power source. The flux-cored wire is melted by an electric arc and deposited layer by layer according to the designed additive path. The substrate is made of rolled Q235 carbon steel with a thickness of 20mm. The additive path is either a double-track single-arc rectangular reciprocating path or a double-track multi-arc rectangular reciprocating path (multiple arcs allow for alternating arc initiation, ensuring uniform heat distribution), such as... Figure 2 As shown, the starting point for the arc can be point A at the lower left corner of the rectangle. Moving right along the length of the rectangle to point B completes the first pass of the double arc. Then, moving along the width of the rectangle to point C, and then moving left along the length of the rectangle to point D completes the second pass. The molten pool of the second pass partially covers the edge of the solidified first pass, forming an overlap area (e.g., ...). Figure 2 (The shaded area in the middle). And when the current layer is deposited and the temperature of the current layer is 150~170℃, the next layer is deposited, until the homogeneous and heterogeneous stainless steel component is obtained.

[0026] The process parameters for arc additive manufacturing in this embodiment are as follows: The initial wire feed speed is 8 m / min, and after 5 reciprocating layers, the wire feed speed becomes 6.5 m / min; the welding torch moving speed is 6 mm / s; pure CO2 is used as the shielding gas, and the gas flow rate is 20 L / min.

[0027] Metallographic and tensile test specimens were taken from the homogeneous stainless steel component prepared in this embodiment along the deposition direction. The metallographic specimens were 10×10×20 mm in size, and the tensile test specimens were standard M10 Φ5 tensile specimens. The metallographic specimens were first ground and polished, then electrolytically etched with oxalic acid for 20 seconds, and finally their microstructure was observed using an optical microscope. The microstructure observed under the optical microscope is shown below. Figure 1 As shown, this is a layered multi-scale heterogeneous structure with alternating coarse-grained and fine-grained regions along the deposition direction. Example 2

[0028] The austenitic stainless steel flux-cored wire was dried in a drying oven at 90℃ for 3.5 hours. The stainless steel flux-cored wire comprises the following components by mass percentage: C≤0.05%, N: 0.2-0.5%, Mn: 0.3-0.6%, Mo: 0.05-0.3%, Cr: 19-25%, Ni: 9-14%, S≤0.003%, P≤0.003%, O≤0.003%, and Fe as the balance.

[0029] Then, due to the inherent characteristics of the flux-cored wire, arc additive manufacturing was performed using the FCW-HardFacing mode of the Fronius-CMT welding power source. The flux-cored wire was melted by an electric arc, and layers were deposited sequentially according to the designed additive path. The substrate was made of rolled Q235 carbon steel with a thickness of 20mm. The additive path was a double-pass, single-arc rectangular reciprocating path (same as the additive path in Example 1). The second weld pool partially covered the edge of the first solidified weld bead, forming an overlap area. When the previous layer was deposited and its temperature was 140~155℃, the next layer was deposited until a homogeneous, heterogeneous stainless steel component was obtained.

[0030] The process parameters for arc additive manufacturing in this embodiment are as follows: The initial wire feed speed was 8.5 m / min, and after four reciprocating layers, the wire feed speed became 6 m / min; the welding torch moving speed was 5.5 mm / s; pure CO2 was used as the shielding gas, and the gas flow rate was 18 L / min.

[0031] Metallographic and tensile test specimens were taken from the homogeneous stainless steel component prepared in this embodiment along the deposition direction. The metallographic specimens were 10×10×20 mm in size, and the tensile test specimens were standard M10 Φ5 tensile specimens. The metallographic specimens were first ground and polished, then electrolytically etched with oxalic acid for 20 seconds, and finally their microstructure was observed using an optical microscope. The microstructure observed under the optical microscope is shown below. Figure 3 As shown, this is a layered multi-scale heterogeneous structure with alternating coarse-grained and fine-grained regions along the deposition direction. Example 3

[0032] Place the existing 308L stainless steel solid wire in a drying oven and dry it at 95°C for 3 hours.

[0033] Then, due to the inherent characteristics of solid wire, arc additive manufacturing was performed using the CrNi199 mode of the Fronius-CMT welding power source. The solid wire was melted by an electric arc, and layers were deposited layer by layer according to the designed additive path. The substrate was made of rolled Q235 carbon steel with a thickness of 20mm. The additive path was a double-pass, single-arc rectangular reciprocating path (same as the additive path in Example 1). The second weld pool partially covered the edge of the first solidified weld, forming an overlap area. When the previous layer was completed and its temperature was 140~155℃, the next layer was deposited until a homogeneous heterogeneous stainless steel component was obtained.

[0034] The process parameters for arc additive manufacturing in this embodiment are as follows: The initial wire feed speed was 8 m / min, and after 6 layers of reciprocating motion, the wire feed speed became 6 m / min; the welding torch moving speed was 6.5 mm / s; pure CO2 was used as the shielding gas, and the gas flow rate was 22 L / min.

[0035] Metallographic and tensile test specimens were taken from the homogeneous stainless steel component prepared in this embodiment along the deposition direction. The metallographic specimens were 10×10×20 mm in size, and the tensile test specimens were standard M10 Φ5 tensile specimens. The metallographic specimens were first ground and polished, then electrolytically etched with oxalic acid for 20 seconds, and finally their microstructure was observed using an optical microscope. The microstructure observed under the optical microscope is shown below. Figure 4 As shown, this is a layered multi-scale heterogeneous structure with alternating coarse-grained and fine-grained regions along the deposition direction. Comparative Example 1

[0036] Place the existing 308L stainless steel solid wire in a drying oven and dry it at 95°C for 3 hours.

[0037] Then, due to the inherent characteristics of solid wire, arc additive manufacturing was performed using the CrNi199 mode of the Fronius-CMT welding power source. The solid wire was melted by an electric arc, and layers were deposited layer by layer according to the designed additive path. The substrate was made of rolled Q235 carbon steel with a thickness of 20mm. The additive path was a single-pass oscillating reciprocating path; when the previous layer was deposited and its temperature was 140~155℃, the next layer was deposited, until a homogeneous heterogeneous stainless steel component was obtained.

[0038] The process parameters for arc additive manufacturing in this comparative example are as follows: The initial wire feed speed was 7 m / min, and after 6 layers of reciprocating motion, the wire feed speed became 5.5 m / min; the welding torch moving speed was 6.5 mm / s; pure Ar was used as the shielding gas, and the gas flow rate was 22 L / min.

[0039] Tensile test specimens were taken from the homogeneous and heterogeneous stainless steel components prepared in this comparative example along the deposition direction. The tensile test specimens were M10 Φ5 standard tensile test specimens.

[0040] The bar tensile specimens prepared in the above embodiments and comparative examples were subjected to tensile property tests on a tensile testing machine conforming to international standards at a slow strain rate of 0.5 mm / min. The tensile property data are shown in Table 1.

[0041] Table 1: Tensile properties of bar tensile specimens from each embodiment and comparative example

[0042] Furthermore, in the arc additive manufacturing process, each embodiment of the present invention employs path design to coordinate the interlayer temperature control coupling process, achieving a special structural coordination of uniform fine grains in the center of the stacked component and alternating coarse and fine grains on both sides. For example... Figures 5-7 As shown, in the central region of the component, due to the design of the additive manufacturing path, the heat source is uniformly superimposed, the interlayer temperature is stable, and the molten pool cooling rate is moderate. Continuous dynamic recrystallization inhibits grain coarsening, thus forming a homogeneous equiaxed fine-grained structure. In the two lateral regions of the component, the difference in boundary heat dissipation and periodic thermal cycling cause single-layer heat accumulation, leading to grain coarsening in the heat-affected zone, thus forming a coarse-grained region. Interlayer temperature control combined with subsequent arc heating causes localized remelting on the surface of the molten layer, followed by rapid solidification, resulting in the formation of fine equiaxed grains in the remelted area, thus forming a fine-grained region. This cycle repeats, ultimately forming a layered, multi-scale homogeneous heterogeneous structure in the component's deposition direction, with a central fine-grained region and alternating coarse-grained and fine-grained regions on both sides.

[0043] The homogeneous-heterogeneous structure enhances the overall mechanical properties of the component: the fine-grained region in the center achieves a synergistic improvement in strength and plasticity, while the layered structure with alternating coarse-grained and fine-grained regions on both sides provides plasticity through coordinated deformation in the coarse-grained region under stress, and strength by hindering dislocation movement in the fine-grained region. Ultimately, this fundamentally reconciles the contradiction between strength and plasticity, enabling the component to achieve high strength while maintaining excellent plastic deformation capacity and toughness: tensile strength ≥530 MPa, yield strength ≥350 MPa, and elongation can still be maintained above 60%.

Claims

1. An additive forming process for homogeneous and heterogeneous stainless steel, characterized in that: Arc additive manufacturing is employed, which uses an electric arc to melt austenitic stainless steel wire and deposits it layer by layer along a double-pass single-start rectangular reciprocating path or a double-pass multi-start rectangular reciprocating path. In each layer, the second molten pool partially covers the edge of the first solidified weld bead, forming an overlap area. When a single layer is deposited and the temperature of that layer is 130~180℃, the next layer is deposited until completion, resulting in a homogeneous heterogeneous stainless steel component. In the component, the middle part, which is composed of the overlapping area of ​​each layer, is a uniform fine-grained structure, and the two sides of the middle part are coarse-grained areas and fine-grained areas are alternately distributed along the stacking direction. Austenitic stainless steel wire comprises the following components by mass percentage: C≤0.05%, N: 0.2%<N≤0.5%, Mn: 0.3-0.6%, Mo: 0.05-0.3%, Cr: 19-25%, Ni: 9-14%, S≤0.003%, P≤0.003%, O≤0.003%, and Fe as the balance.

2. The additive manufacturing process according to claim 1, characterized in that: The process parameters for arc additive manufacturing are as follows: welding torch moving speed is 5~10mm / s, wire feeding speed is 4~8m / min, shielding gas is CO2 or pure Ar, gas flow rate is 15~25L / min, and dry extension is 12~20mm.

3. The additive manufacturing process according to claim 1, characterized in that: Before arc additive manufacturing, the stainless steel wire is dried at 70~120℃ for 3~5 hours.

4. The additive manufacturing process according to claim 1, characterized in that: The grain size in the coarse-grained region is 1300~1800μm, and the grain size in the fine-grained region is 200~450μm.

5. The additive manufacturing process according to any one of claims 1 to 4, characterized in that: The component has a tensile strength ≥530MPa, a yield strength ≥350MPs, and an elongation ≥60%.

Citation Information

Patent Citations

  • Method for preparing lamellar isomeric light alloy plate through asymmetric accumulative ply rolling process

    CN113649413A

  • Arc-welding material additive manufacturing method for stainless steel part

    CN105921851A

  • Electric arc additive manufacturing and testing method of duplex stainless steel

    CN114101855A

  • 15-5PH stainless steel and additive manufacturing method and application thereof

    CN117961088A